Governance for Sustainability of Rural Water Supply and Sanitation Schemes (RWSS): Case from NAPA WASH - Adhikari, Keshab Prasad (Nepalese Journal of Development and Rural Studies, 2020)
Water and sanitation are taken at the heart of achieving a number of goals and critical targets of sustainable development goals. But achieving sustained water and sanitation service in a rural context is problematic from the viewpoint of technical, financial, environmental, and social, and governance aspects of functionality. Therefore, good governance in the operation and management of rural water and sanitation schemes are a key component to determine the other aspects of functioning and longer-term sustainability. The study sees the working of five indicators of functionality, five layers of priority ranking indicators, four service indicators of quantity, accessibility, reliability, and quality (QARQ), and ten indicators of assessing governance level sustainability. In all aspects of assessment, most RWSS found to stand at the level of partial sustainability. This urged for giving higher priority to upgrading such schemes in the status of full sustainability.